2012
DOI: 10.1016/j.ajhg.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Global Rare Copy-Number Variants to the Risk of Sporadic Congenital Heart Disease

Abstract: Previous studies have shown that copy-number variants (CNVs) contribute to the risk of complex developmental phenotypes. However, the contribution of global CNV burden to the risk of sporadic congenital heart disease (CHD) remains incompletely defined. We generated genome-wide CNV data by using Illumina 660W-Quad SNP arrays in 2,256 individuals with CHD, 283 trio CHD-affected families, and 1,538 controls. We found association of rare genic deletions with CHD risk (odds ratio [OR] = 1.8, p = 0.0008). Rare delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
232
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(254 citation statements)
references
References 59 publications
18
232
3
1
Order By: Relevance
“…Thus, TGA could result from a genetic predisposition related to many low impact, mostly inherited, variants associated to environmental factors. The frequency of de novo CNVs identified in patients with ToF (6.6%) is broadly similar to previously reported frequencies 11,21 considering the differences in the arrays and analysis pipelines between the studies. For example, Greenway et al 11 reported 10% of de novo CNVs in their ToF patients' cohort, which is slightly more than what we observed.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, TGA could result from a genetic predisposition related to many low impact, mostly inherited, variants associated to environmental factors. The frequency of de novo CNVs identified in patients with ToF (6.6%) is broadly similar to previously reported frequencies 11,21 considering the differences in the arrays and analysis pipelines between the studies. For example, Greenway et al 11 reported 10% of de novo CNVs in their ToF patients' cohort, which is slightly more than what we observed.…”
Section: Discussionsupporting
confidence: 72%
“…Recurrent deletions and duplications at this locus have been associated with both syndromic and nonsyndromic forms of CHD, including ToF. 11,21,36 Because the GJA5 mutant mice exhibit a wide range of CHD, among them conotruncal defects, 37 the gene seems to be a good candidate for the cardiac malformations, although no point mutations have been identified in patients yet.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide [20][21][22] and gene-centric 23 copy number variants (CNV) were tested on a series of CHD with criteria to infer causality based either on de novo deletion/duplication in sporadic cases or familial segregation in multiplex cases. These studies could confirm the involvement of known CHD genes and discover new genes and genomic regions.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Rare CNVs 7 and syndromal (extracardiac) features 7,12 could influence reproductive fitness and transmission patterns in TOF, as is the case with 22q11.2 deletions and the associated 22q11.2 deletion syndrome (22q11.2DS). [13][14][15][16][17][18] Furthermore, an understanding of typical familial segregation patterns and other aspects of family history would help with the interpretation of emerging and novel molecular genetic risk factors (both de novo and inherited) for TOF.…”
Section: Clinical Perspective On P 109mentioning
confidence: 99%